Judul: Memahami Faktor Pemilihan Moda pada Peyedia Otobus Gunung Harta dan Komitmennya terhadap Kenyamanan - Budi Mardikawati; I Putu Bagus Yudastara; I Made Yogi Wiswantara; M.Siraj Arkhan Daffa Hidoyo; Devanty Eka Hapsari; Darin Aqilah; Kadek Cakra Wisnu Mukti; Kadek Ayu Sutrisna Dewi; Lia Agistin BR Pangaribuan (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This article aims to explain the implementation of socialization activities on factors for choosing transportation modes, especially at the Gunung Harta Autobus Company (PO), with the dominant factor being passenger comfort. The socialization method used is direct counseling for staff, drivers, and passengers at PO Gunung Harta. PO Gunung Harta's commitment to passenger comfort can be seen in various initiatives and consistency, such as the number of passengers carried according to bus capacity, main facilities in the form of luggage racks, and additional facilities in the form of window film and audiovisual facilities placed in the passenger room. It is hoped that this commitment will become a reference for other POs in improving services to provide a comfortable mode of transportation. It is hoped that the results of the outreach will increase public awareness about the importance of driving safely and wisely when choosing modes of transportation in order to create safer and more comfortable travel for all.